Managed Labor Migration in Afghanistan : Identifying Host Countries for Managed Migration from Afghanistan - Smith, Rebekah (World Bank, Washington, DC, 2018)
Foreign labor markets offer an excellent opportunity to improve employment and income outcomes for a country’s workforce. However, if a sending country’s workforce abroad is overly concentrated in a few receiving markets, it runs the risk of becoming dependent on conditions within those markets for employment opportunities and remittances for its workforce. A more managed migration approach to select higher-income host countries promises higher and more regular levels of remittances per capita through more formal channels, with expectations of skill improvements upon departure and after return. Currently, Afghanistan’s workforce abroad is highly concentrated in Iran and Pakistan. This paper proposes a methodology for assessing potential expansion into new foreign labor markets, and applies said methodology to potential new labor markets for Afghan workers (including Malaysia, Europe, Australia, Central Asia, and Turkey, and expansion in Pakistan, Iran, and Gulf Cooperation Council (GCC) countries). The findings indicate that GCC countries and Turkey are the most viable markets for absorbing Afghan workers in the coming years.